IDIOM ‘SARU’ SEBAGAI REFLEKSI KONSEP PEMIKIRAN MASYARAKAT JEPANG TERHADAP MONYET - Devita Widyaningtyas Yogyanti (IZUMI, 2018)
(Title: Idiom ‘Saru’ as a Reflection of Japanese People Thinking Concept Towards Monkey ). This research is an anthropological linguistic study that is conducted by examining the idioms that use the word "saru" (monkey) as the object of study. This study aims at analyzing the basic concepts of people's thought about the word "saru" (monkey) through the use of its idioms. The researcher collected the data of the idioms that use the word "saru" through literature studies that cover the literature containing Japanese idioms and interviews of Japanese people living in Yogyakarta. The focus of this research is the correlation between literal meaning and metaphorical meaning in idioms that contain the word "saru". The correlation of the meaning is traced using a diachronic perspective to see the concept of Japanese people's thought towards monkeys. According to the results of the study, the researcher found 11 idioms that use the word "saru", namely Sansaru, Sarugi, Sarugutsuwa, Sarushibari, Sarutsunagi, Sarujie, Sarugashikoshi, Sarumane, Sarushibai, Saruboo, and Saruni. From the relationship between the literal meaning and the metaphorical meaning of the 11 idioms, the result shows that Japanese people have 3 concepts towards monkey, which are as a holy and sacred animal, as an animal that possesses the magical power to make something quiet, and as an animal resembling the human being. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor